Folic‐Acid‐Mediated Functionalized Gold Nanocages for Targeted Delivery of Anti‐miR‐181b in Combination of Gene Therapy and Photothermal Therapy against Hepatocellular Carcinoma. (9th February 2016) - Huang, Shengnan; Duan, Shaofeng; Wang, Jing; Bao, Shijin; Qiu, Xiaojing; Li, Chunming; Liu, Ying; Yan, Lijuan; Zhang, Zhenzhong; Hu, Yurong
Abstract : Therapeutic strategies based on modulation of microRNAs (miRNAs) activity hold much promise for cancer therapy, but for clinical applications, the efficient delivery of miRNAs to tumor cells or tumor tissues remains a great challenge. In this work, microRNA‐181b inhibitor (anti‐miR‐181b) is successfully condensed into polyethyleneimine (PEI)‐modified and folate receptor (FR)‐targeted PEGylated gold nanocages (AuNCs). This delivery system is designated as anti‐miR‐181b/PTPAuNCs nanocomplexes (PTPAuNC‐NPs), which begin with chemical modification of AuNCs with SH‐PEG5000 ‐folic acid (SH‐PEG5000 ‐FA) and SH‐PEG5000 through a gold–sulfur bond, followed by conjugating PEI using lipoic acid as a linker. Finally anti‐miR‐181b is condensed via electrostatic interactions. In vitro and in vivo experiments show that PTPAuNC‐NPs can efficiently deliver anti‐miR‐181b into target sites to suppress tumor growth, and considerably decrease tumor volumes in SMMC‐7721 tumor‐bearing nude mice under near‐infrared radiation. All these results suggest that PTPAuNC‐NP gene delivery system with combination of gene therapy and photothermal therapy will be of great potential use in future cancer therapy. Abstract : Gold nanocages (AuNCs), after chemical modification with polyethyleneimine, PEG, and lipoic acid, efficiently deliver anti‐miR‐181b into target sites to suppress tumor growth, and considerably decreases tumor volumes in SMMC‐7721 tumor‐bearing nude mice under near‐infrared radiation. Thus, the anti‐miR‐181b/PTPAuNCs‐mediated synergistic therapeutic strategy would be of great potential use in future cancer therapy.